First record and a new species of the fossil dragonfly genus Proinogomphus (Odonata: Liassogomphidae) from the Early Jurassic of Bascharage in the Grand Duchy of Luxembourg - Bechly, Günter (Zootaxa, 2018)
A new species of fossil dragonfly, Proinogomphus kreuzerorum sp. nov. (Liassogomphidae), is described from the Early Jurassic black shale of Bascharage in the Grand Duchy of Luxembourg, based on a very well-preserved isolated female hind wing. This genus was previously only known from the Liassic of Braunschweig region in Germany, and is here recorded for the first time for this fossil locality. The classification of the family Liassogomphidae Tillyard, 1935 and the genus Proinogomphus Cowley, 1942 is briefly discussed and the diagnosis of the latter is emended.